2007
DOI: 10.1016/j.neulet.2007.02.077
|View full text |Cite
|
Sign up to set email alerts
|

Iron, copper, and iron regulatory protein 2 in Alzheimer's disease and related dementias

Abstract: Accumulating evidence implicates a role for altered iron and copper metabolism in the pathogenesis of neurodegenerative disorders such as Alzheimer's disease (AD). However, imbalances in the levels of the various forms of iron at different stages of AD have not been examined. In this pilot study we extracted and measured the levels of loosely bound, non-heme and total iron and copper in the frontal cortex and hippocampus of patients with mild-moderate AD (n=3), severe AD (n=8) and dementia with Lewy bodies (DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 28 publications
0
66
1
Order By: Relevance
“…Our current data indicate that lipid rafts provide a favorable environment for the co-enrichment of copper and A␤, especially under conditions of copper deficiency. We hypothesize that in aging and AD, where there is intracellular copper deficiency (5,6,69), the concomitant enrichment of A␤ and copper within lipid rafts promotes the formation of redoxactive A␤⅐Cu 2ϩ complexes, fostering the catalytic oxidation of cholesterol, lipid, and the generation of neurotoxic H 2 O 2 . This further creates a vulnerable environment for A␤ to cross-link, forming SDS-resistant oligomers characteristic of A␤ extracted from AD brains (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…Our current data indicate that lipid rafts provide a favorable environment for the co-enrichment of copper and A␤, especially under conditions of copper deficiency. We hypothesize that in aging and AD, where there is intracellular copper deficiency (5,6,69), the concomitant enrichment of A␤ and copper within lipid rafts promotes the formation of redoxactive A␤⅐Cu 2ϩ complexes, fostering the catalytic oxidation of cholesterol, lipid, and the generation of neurotoxic H 2 O 2 . This further creates a vulnerable environment for A␤ to cross-link, forming SDS-resistant oligomers characteristic of A␤ extracted from AD brains (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…Many DLB subjects have dementia and depression resulting from possible degeneration of cholinergic, noradrenergic and serotonergic neurons. In both AD and DLB, accumulation of iron is found inside some melanin-containing dopaminergic neurons and inside amyloid plaques and neurofibrillary tangles [40]. It has been suggested that iron accumulation may contribute to the oxidative stress-induced apoptosis reported in both diseases [41].…”
Section: Metal Chelators/mao-b Inhibitors With Additional Cotargeted mentioning
confidence: 99%
“…In addition, A␤ is able to catalyze the reduction of Cu(II) and Fe(III), generating reactive oxygen species that contribute to the oxidative stress observed in the AD brain (8 -14). Paradoxically, there is evidence of copper deficiency in neighboring cells (15)(16)(17)(18), compromising the activity of copper-dependent enzymes, such as cytochrome c-oxidase and copper/zinc-superoxide dismutase (SOD1), which are essential for cellular respiration and as antioxidant defense, respectively (19 -21). Restoration of copper balance using ionophores (22), such as clioquionol and PBT-2, has shown promising results in both animal and human trials (23)(24)(25)(26).…”
mentioning
confidence: 99%